Anti-aging effect of TMQ on EPDM for Various Cure Systems - Şehriban Öncel; Bağdagül Karaağaç; Hakan Erdoğan; Mahir Burak Efe; Gürcan Gül (Journal of Advanced Research in Natural and Applied Sciences)
Ethylene propylene diene rubber (EPDM) is a common raw material for weather resistant rubber products used in lots of areas such as cable, automotive, marine industry and aviation applications. Superior processing behaviour, electrical properties and moderate high temperature resistance also make EPDM an attractive raw material for a wide range of further industrial performance requirements. As well as the other general purpose rubbers, EPDM needs to be protected against thermo-oxidative aging. Short and long term aging behaviour of both sulphur and peroxide cured EPDM has been studied in literature. However, to the authors’ best knowledge, there is not any study in literature systematically evaluating a common rubber antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline (TMQ) for investigating theoretical life-time of EPDM based materials that were vulcanized with different crosslinking systems. In this study, effects of TMQ on the thermo-oxidative resistance of EPDM has been studied for conven-tional and efficient sulphur vulcanization systems as well as peroxide vulcanization system. Aging mechanism for different cases has been investigated by using structural, rheological and mechanical tests. Thermo-oxidative aging has been monitored by carbonyl index and activation energy. Arrhenius based life-time estimation methodology has also been employed to evaluate aging behaviour of the reference and TMQ containing (-T) compounds. TMQ was found to exhibit different levels of protection against thermo-oxidative aging for all the curing systems and at all aging conditions. Higher aging activation energy for -T compounds has been attributed to extended service life of the material in the presence of TMQ.